Analisis Kemampuan Pemecahan Masalah Matematika dalam Menyelesaikan Soal Cerita Berdasarkan Prosedur Polya - Yuwono, Timbul; Supanggih, Mulya; Ferdiani, Rosita Dwi (Jurnal Tadris Matematika, 2018)
The purpose of this study is to analyze mathematical problem-solving abilities based on Polya's steps and the causes of students' errors in solving mathematical problems. The problem-solving stage consists of 4 stages, namely the stage of understanding the problem, planning a solution, carrying out a solution plan, and looking back. This study used 6 subjects from 25 eighth grade students of SMP Terpadu Turen. Data collection is done by tests and interviews. Data validity test is done by triangulation technique. The results of this study were (1) at the stage of understanding many students, they did not experience difficulties because students were able to understand the problem, (2) at the planning stage there were some students who did not write the completion plan but understood the way they would do to solve the problem but they were not used to write down the plan, (3) at the stage of carrying out the plan there were some students who have difficulty because they are less thorough so that they are not aware of the mistakes made. This is because students lack concentration in solving problems, (4) at the stage of looking back there are students who have not reached this stage because they have not completed the previous stage.